ETALASE DIGITAL SENI TRADISI: REPRESENTASI DAN NEGOSIASI MAKNA PELESTARIAN BUDAYA JAWA TIMUR DI INSTAGRAM @cak_durasim - Muhamad Farhan Nudin; Zainal Abidin Achmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the rapid transformation of digital media and its impact on how local culture is represented and negotiated on social media, specifically looking at the challenges of maintaining cultural authenticity for Generation Z. The objective of this research is to analyze the cultural communication practices, representations, and meaning-making processes regarding the preservation and revitalization of East Javanese arts on the Instagram account @cak_durasim. Utilizing a qualitative methodology with Christine Hine’s virtual ethnography approach, data were gathered through online participant observation and in-depth interviews with two account managers and five active followers. The collected data were analyzed using Miles and Huberman’s interactive model, comprising data reduction, data display, and conclusion drawing. The results indicate that the @cak_durasim account functions effectively as a digital cultural showcase ("etalase"), bridging high-context traditional arts with low-context digital platforms through visually appealing and simplified narrative adaptations tailored to Gen Z without abandoning core cultural rules ("pakem"). Furthermore, digital interactions reflect active audience reception; while "likes" signify superficial initial interest, the comment section serves as a dynamic space for critical negotiation, collaborative knowledge enrichment, and local identity affirmation. However, while digital documentation successfully expands cultural reach and awareness, it cannot completely substitute the emotional depth and experiential value of live physical performances.